Pengaruh Prosentase Campuran Briket Limbah Serbuk Kayu Gergajian Dan Limbah Daun Kayuputih Terhadap Nilai Kalor Dan Kecepatan Pembakaran - Malakauseya, Jeffrie Jacobis; Sudjito, Sudjito; Sasongko, Mega Nur (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Briquette is one of alternative energy. Raw material briquettes can be derived from agricultural waste and forestry plantations. Many factors that influence on briquette such as the type of materials, adhesives and pressure others. Adhesives used are sago starch waste that has been disposed and can no longer be consumed by humans. Raw material briquettes from waste of sawdust and sawn eucalyptus leaves. Pressure briquette of 30 PSI. Both raw material briquettes sieved with 20 mesh sieve qualify. From the results, the average calorific value of briquettes is the highest of 4896.16 calories / gram at 40% mixture of sawdust sawn 60% powder mixed with eucalyptus leaves. Percentage of ash content lowest average was 2.17%.Keywords : Briquette, adhesive, sawdust, eucalyptus.